Identification of Protease-Producing Halophilic Bacteria Isolated from Salt-Pond Soil - Asep Awaludin Prihanto; Rahmi Nurdiani; Hidayatun Muyasharoh; Jauharotul Afifah (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
Highlights • The halophilic bacteria were isolated from salt-pond soil. • Isolate C2 was identified as the best protease producer. • Isolate C2 was identified as B. amyloliquefaciens strain UBC